Effect of resection depth of early glottic cancer on vocal outcome: An optimized finite element simulation. (22nd May 2015) - Mau, Ted; Palaparthi, Anil; Riede, Tobias; Titze, Ingo R.
<x xml:space="preserve">Abstract</x> Objectives/Hypothesis To test the hypothesis that subligamental cordectomy produces superior acoustic outcome than subepithelial cordectomy for early (T1–2) glottic cancer that requires complete removal of the superficial lamina propria but does not involve the vocal ligament. Study Design Computer simulation. Methods A computational tool for vocal fold surgical planning and simulation (the National Center for Voice and Speech Phonosurgery Optimizer‐Simulator) was used to evaluate the acoustic output of alternative vocal fold morphologies. Four morphologies were simulated: normal, subepithelial cordectomy, subligamental cordectomy, and transligamental cordectomy (partial ligament resection). The primary outcome measure was the range of fundamental frequency (F0) and sound pressure level (SPL). A more restricted F0‐SPL range was considered less favorable because of reduced acoustic possibilities given the same range of driving subglottic pressure and identical vocal fold posturing. Results Subligamental cordectomy generated solutions covering an F0‐SPL range 82% of normal for a rectangular vocal fold. In contrast, transligamental and subepithelial cordectomies produced significantly smaller F0‐SPL ranges, 57% and 19% of normal, respectively. Conclusion This study illustrates the use of the Phonosurgery Optimizer‐Simulator to test a specific hypothesis regarding the merits of two surgical alternatives. These simulation results provide theoretical support for vocal ligament excision with maximum muscle preservation when superficial lamina propria resection is necessary but the vocal ligament can be spared on oncological grounds. The resection of more tissue may paradoxically allow the eventual recovery of a better speaking voice, assuming glottal width is restored. Application of this conclusion to surgical practice will require confirmatory clinical data. Level of Evidence N/A. Laryngoscope, 125:1892–1899, 2015